2004
DOI: 10.1603/0022-0493-97.2.192
|View full text |Cite
|
Sign up to set email alerts
|

Bean Leaf Beetle (Coleoptera: Chrysomelidae) Management for Reduction of Bean Pod Mottle Virus

Abstract: Bean pod mottle virus (BPMV) is a management concern for soybean, Glycine max (L.), producers in the North Central states because it can cause yield loss and reduce seed quality by induction of seed coat mottling. The main vector of BPMV is the bean leaf beetle, Cerotoma trifurcata (Forster). An experiment was conducted in 2000 and 2001 at two locations in northwestern and central Iowa to test three insecticide treatments for suppression of bean leaf beetles, and subsequently, BPMV. Treatments of insecticide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 22 publications
3
27
0
Order By: Relevance
“…In 2002 and 2003, seed tests were conducted for both BPMV and SMV because of increased populations of the soybean aphid and the inability to discern BPMV from SMV based on symptoms on foliage or seed (Tables 2 and 3). In 2002, based on reports that well-timed application of foliar insecticide may reduce final disease incidence and improve yield and seed quality (Krell et al, 2004), an additional set of seeds of the soybean cultivars selected for the 2001 test was treated with the insecticide imidacloprid to reveal any effect on the characters measured. Although application of imidacloprid as a seed treatment may reduce beetle populations after emergence (Cullen et al, 2003), pairwise comparisons of these cultivars in 2002 showed no significant differences (t test, P 5 0.05) in all characters measured for each soybean cultivar (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…In 2002 and 2003, seed tests were conducted for both BPMV and SMV because of increased populations of the soybean aphid and the inability to discern BPMV from SMV based on symptoms on foliage or seed (Tables 2 and 3). In 2002, based on reports that well-timed application of foliar insecticide may reduce final disease incidence and improve yield and seed quality (Krell et al, 2004), an additional set of seeds of the soybean cultivars selected for the 2001 test was treated with the insecticide imidacloprid to reveal any effect on the characters measured. Although application of imidacloprid as a seed treatment may reduce beetle populations after emergence (Cullen et al, 2003), pairwise comparisons of these cultivars in 2002 showed no significant differences (t test, P 5 0.05) in all characters measured for each soybean cultivar (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…A single beetle per square metre can cause yield losses of 3 kg ha À1 through pod damage (Smelser & Pedigo, 1992). The bean leaf beetle is also the primary vector of bean pod mottle virus and transmission of this virus to soybean can cause seed discolouration and further yield reduction (Krell et al, 2003(Krell et al, , 2004Bradshaw et al, 2008). An additional issue is the lack of consistent biological control.…”
Section: Introductionmentioning
confidence: 99%
“…Many viruses are spread by insect vectors between and within crops. Strategies which suppress insect populations below a threshold level could potentially reduce the damage caused by transmitted plant viruses [8]. Aphids, mites and nematodes are the largest and most significant insect vectors.…”
Section: Introductionmentioning
confidence: 99%